Nutritional availability and carbon footprints of omnivorous, vegetarian and vegan diets: A cross-sectional analysis of dietary data for UK children aged 2–12 - Alice Coffey; Robert Lillywhite; Oyinlola Oyebode (PLoS ONE, 2026)
As plant-based (PB) diets become more common among UK children, understanding their nutritional adequacy and environmental impact is vital. This study addresses that lack of understanding through assessment of the nutrient content and greenhouse gas emissions for omnivorous, vegetarian, and vegan diets. A cross-sectional analysis was conducted using three-day weighed food diaries from 39 UK children aged 2–12 years (omnivore n = 15; and PB: vegetarian n = 11; vegan n = 13). Nutrients were analysed with and without supplementation using Nutritics software. GHG emissions were calculated at the ingredient level (kgCO₂e/day) and grouped by Eatwell Guide food categories. No dietary group met all nutrient reference values. Omnivores exceeded recommended intakes for saturated fat and free sugars while failing to meet the recommended intake for fibre, whereas PB children had intakes of these nutrients in the healthy range. PB diets were adequate in protein and vitamin B12 even in the absence of supplementation. Vegan children also met iron requirements from diet alone, whereas omnivore and vegetarian children did not meet iron targets without supplementation. Vitamin D intake was insufficient across all groups when supplements were excluded, with only vegan children achieving recommended levels through supplementation. Zinc requirements were met only by vegetarian children with the aid of supplements and were not met by vegan or omnivore children with or without supplementation. Iodine intake remained inadequate in vegan children even with supplementation. Mean daily greenhouse gas (GHG) emissions differed significantly between diet groups, with omnivores having the highest emissions, while vegans had the lowest emissions: 46% lower than omnivores, and 20% lower than vegetarians. Well-planned PB diets can meet most nutrient needs in UK children when supported by fortified foods and supplements, while substantially reducing dietary GHG emissions compared with omnivorous diets. Shifting away from animal protein and dairy provides an opportunity for improving both nutritional quality and environmental sustainability.